SOCIOPRAGMATIC STUDY OF SPEECH ACTS OF REQUEST OF FISH TRADERS AND FISHERMEN AT FISH AUCTION (TINDAK TUTUR PERMINTAAN ANTARA PENJUAL IKAN DAN NELAYAN DI TEMPAT PELELANGAN IKAN SUATU KAJIAN SOSIOPRAGMATIK ) - Ike Revita; Balazs Huszka (Universitas PGRI Sumatera Barat, 2021)
This study is aimed at describing the speech acts of the request of fish traders as buyers to fishermen as sellers at fish auctions (Tempat Pelelangan Ikan/TPI) at Carocok Port, Koto XI Tarusan District, Pesisir Selatan Regency. The objectives of the study are to identify the modes and the types of requests used by fish traders in the fish auction of Carocok Port. The research is qualitatively conducted. The data were collected by using the observational method with note-taking, recording, and interviewing. 21 informants, 8 fishermen, 10 retailers, and 3 housewives were interviewed to dig information about the reasons for using a certain way of making the request. The analysis was done by determining the criteria of speech acts of the request (Kissine, 2013) (Ike Revita, 2008). The result of the analysis is descriptively done. The percentage was used to identify the number of occurrences of a certain type. After analyzing the data, it is found that the declarative and imperative mode is used more than interrogative and exclamative. Speech acts of a direct request appear more dominant than indirect ones. This implies that the speech acts of the request of fish traders tend to be straightforward, in line with the firmness of bidding the price.